2001
DOI: 10.4319/lo.2001.46.4.0778
|View full text |Cite
|
Sign up to set email alerts
|

Microbial size spectra from natural and nutrient enriched ecosystems

Abstract: Microbial size spectra, including bacteria through nanophytoplankton, were measured by use of flow cytometry across the western north Atlantic Ocean and during two nutrient enrichment studies: bottle enrichments in the Sargasso Sea and an in situ iron enrichment in the equatorial Pacific (IronEx II). Spectral shapes, or the relative conformity to a function described by a power law, ranged from smooth and log linear during the spring bloom in the Sargasso Sea to being distinctly non-log linear in coastal water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
87
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 53 publications
8
87
2
Order By: Relevance
“…Levin et al 1997;Banavar et al 1999;Solé et al 1999;Marquet 2000;Norberg et al 2001), which is routinely observed in marine ecosystems regardless of a wide range of forcing environmental conditions (e.g. Cavender-Bares et al 2001). This feature, the signature of scale invariance, is detected by the regularity of the community size spectrum, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levin et al 1997;Banavar et al 1999;Solé et al 1999;Marquet 2000;Norberg et al 2001), which is routinely observed in marine ecosystems regardless of a wide range of forcing environmental conditions (e.g. Cavender-Bares et al 2001). This feature, the signature of scale invariance, is detected by the regularity of the community size spectrum, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Such distributions emerge as ubiquitous properties of complex marine food webs (e.g. Sheldon et al 1972;Platt 1985;Prothero 1986;Rodriguez & Mullin 1986;Chisholm 1992;Blanco et al 1994;Rodriguez 1994;Vidondo et al 1997;Cavender-Bares et al 2001;Rodriguez et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The value of the size-scaling exponent is strongly related to ecosystem's productivity. Unproductive ecosystems characteristic of subtropical, oligotrophic regions show steeper slopes (21.3 to 21.1) [13,14], whereas in coastal, highly productive ecosystems, the slopes become less negative (20.8 to 20.6), as a result of the increased relative abundance of larger cells [7,15,16]. Despite this connection between ecosystem's productivity and size structure, the origin of the actual values of the size-scaling exponent for phytoplankton cell abundance is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The promise of size spectra as a synoptic measure of structure and function of planktonic communities has long been recognized (e.g., Chisholm 1992) and has been assessed in several studies (Cavender-Bares et al 2001, Sabetta et al 2005), but measurements of particle size distribution (PSD) in general, and phytoplankton size distribution in particular, have always been a challenge. The most commonly practiced laboratory-based measurements such as microscopy or electrical sensing zone particle counters (Coulter, Elzone, flow cytometry), require isolation of particles from the environment and often involve sample preparation (e.g., addition of fixatives) and storage that may alter particle size distribution (MendenDeuer et al 2001).…”
mentioning
confidence: 99%